BAHTSUL MASAIL NU DAN IMPLEMENTASI DEMOKRASI - Muhammad, Husein (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
Democracy is not merely a discourse, but is also something that needs to be implemented in an action. The action of democracy has apparently been practiced in NU organization, one of which is in the form of Bahtsul Masail which is usually done in conjunction with the holding of the congress. The task and function of Bahtsul Masail forum, as stipulated in the Statutes/by-laws are to collect, discuss, and then resolve mauquf (postponed) and waqi'iyyah (casuistic) problems to reach for religious legal certainty. To what degree is the role of the kyais in reaching for the legal certainty, and whether the democratization is really practiced in that forum, for instance, by involving the roles of those outside kyai cycle. This article is an attempt to answer those questions.